Analisis Pengukuran Waktu Baku Untuk Menentukan Tingkat Produktivitas Pada Operator Pemasangan O-Ring Menggunakan Metode Jam Henti (Studi Kasus Di PT Y) - Andrew Sinurat; Sukanta Sukanta (Industrika : Jurnal Ilmiah Teknik Industri, 2023)
With the development of the era of globalization and technological progress, the development of a manufacturer must also increase. One way to increase labour productivity is to calculate standard time. The standard time is the time required reasonably by a normal worker to complete a job that is carried out in the best work system. The research was carried out by direct observation in the field. Observation of the standard time that occurs through a certain time interval is useful for knowing the description of the use of queues. In this study, the population was operators working at PT Y at the time of the study, while the sample used was the total time of O-Ring installation. The analysis method used in this study uses the standard time analysis method using a stopwatch. Adjustments are made as a measuring effort to normalize the average price carried out by the operator. Adjustments are taken into account because operators in the work can do inappropriately, for example too fast as if in a hurry, encounter some difficulties, and other things. Time data collection was carried out 30 times by breaking down the work into three motion elements. The results of the standard time measurement for each motion element are motion element A of 65.125 seconds, motion element B of 463.84 seconds and motion element C of 59.66 seconds. Keywords: Standard Time, Stopwatch Time Study, Work System